The lower symmetry electron-density distribution and the charge transport anisotropy in cubic dodecaboride LuB12. (8th June 2018) - Bolotina, Nadezhda B; Dudka, Alexander P; Khrykina, Olga N; Krasnorussky, Vladimir N; Shitsevalova, Natalya Yu; Filipov, Volodymyr B; Sluchanko, Nikolay E
Abstract: High-quality single crystals of LuB12 are grown using the induction zone melting method. The x-ray data are collected at temperatures 293, 135, 95, 50 K. The crystal structure of LuB12 can be refined with record low R -factor in the cubic Fm m symmetry group despite reiterated observations of the cubic symmetry distortions both in the unit-cell values and in the physical properties. A peculiar computing strategy is developed to resolve this contradiction. True symmetry of the electron-density distribution in LuB12 is proved to be much lower than cubic as a result, which correlates very accurately with anisotropy of transport properties of LuB12 .